PROJECT SCHEDULING ANALYSIS USING PRECEDENCE DIAGRAM METHOD (PDM) - Andani Devi Novitasari; Rina Sandora; Rahandini Lukita Lestari (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2018)
Many obstacles that affect the completion of the project late, like: weather, late general plan approval, late material arrival, less skills and others. The Precedence Diagram Method is the method used to create network planning especially project scheduling. This research will examine how to plan the proper project scheduling of Pressure Vessel project of PT Wika Technip which is done by PT. Barata Indonesia by using PDM.The results obtained from the cost calculation at 252 days of project life have total project cost of Rp.6.131.093.885,00 and at project age 243 days total project cost is Rp.6.236.994.056,00. In this case it is known that there is an increase in total cost of Rp.105.900.171,00 and the time difference of 9 days when the acceleration is done on the project duration from 252 days to 243 days.